Research of a 1st-century BC shipwreck off Cape Letavica on the island of Pag (In situ, 2024)
The shipwreck off Cape Letavica is currently the only well-preserved underwater site in the Croatian waters not protected by an iron cage, where tourist diving is regularly carried out, as well as archaeological research in which all interested divers participate. During the 2023 research campaign, the underwater excavation continued from the southwestern part of the ship in the direction of its central part. A total of thirty-six complete or damaged ceramic vessels were taken out, and twenty discoid ceramic amphora stoppers were also found in the excavation. In the southernmost part of the excavation area, several more complete amphorae were found, so during the next year it will be necessary to continue the research in the direction of the south and east.
Keywords: shipwreck; 1st century BC; amphorae; Lamboglia 2; Pag